IRRADIATION EFFECT ON PEROXIDATION INDEX ON OKARABASED SOYBEAN FLOUR - Ana Paula Nunes (Brazilian Journal of Radiation Sciences)
Soya seasoned flour (SSF), also known as “farofa”, is an industrialized product, low cost, easy to make and can be enriched in order to provide a food with greater nutritional and functional value. In this regard, “okara” (inert flavored mass obtained as a residue from the soybean extract), is a viable alternative for nutritional enrichment in relation to conventional maize and manioc tempered flours and ionizing radiation process increases its conservation. The present work aimed to use the SSF based “okara”, as a way to reuse a by-product of soybean processing and analyzing the possible effect of gamma irradiation at doses of 1 and 3 kGy, in the analysis of determination of lipid peroxidation. The preparation of SSF containing “okara”, dehydrated condiments and flavor uplifting was held at FATEC Marília. SSF samples were processed at “Centro de Energia Nuclear na Agricultura (CENA)”, University of Piracicaba-SP, irradiated with doses of 1 and 3 KGy in 60Co source. The dose rate was 0.269/hs. Analyses were performed to determine the peroxide index of control samples and irradiated in triplicate in 1, 15, 30 and 45 storage days in accordance with methodology for oils and fats with modifications. Using this peroxides methodology, it wasn’t possible to detect changes in oxidative quality in SSF samples, within 45 days of storage, with the parameter that the flour showed 29.92% of lipids. We conclude that this product with excellent nutritional attributes about the commercial flour, we must apply a different methodology to detect any radiation damage on lipid compounds.